Implementasi pembelajaran berbasis High Order Thinking Skills (HOTS) Mahasiswa Kelas 4D PGSD Universitas Muhammadiyah Surakarta - Anayanti, Dinda Kestu; Dini, Faza Shafira; Putri, Sekar Destina; Sari, Latifah Elfrida; Hanifah, Habila Hajar (Nur Science Institute, 2024)
One of the developments in the current education assessment system in Indonesia is the implementation of higher-order thinking (HOTS)-based learning, which requires students to have high-level thinking skills. In the world of education, HOTS is the ability of students to think that they not only remember but are also expected to be able to develop ideas. The purpose of this study was to measure the level of success and develop critical, logical, reflective, metacognitive, and creative thinking skills in the implementation of mathematics learning based on higher-order thinking (HOTS). This study is quantitative, using an evaluation method and using a sampling method using Simple Random Sampling on the Spin Wheel application. The results of the analysis showed that the Higher Order Thinking Skills (HOTS) ability of UMS PGSD students was in the High category with a percentage of 77 percent. So, the implementation of HOTS learning in PGSD class 4D students at the University of Muhammadiyah Surakarta was successful. Students tend to have high HOTS thinking skills but still need to improve in answering domain questions (C4 & C6) on mixed arithmetic operations and distance and speed.